THE INFLUENCE OF PARENTAL SUPPORT AND GIVING OF REWARDS ON THE LEARNING ACHIEVEMENT OF CLASS IV ELEMENTARY SCHOOL STUDENTS - Aprilia Gustin Nur Pratiwi; Zainal Arif; Anip Dwi Saputro (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Based on the results of the preliminary study conducted, there was a very drastic decrease in learning achievement in class IV students at SD Muhammadiyah 3 Bungkal. One of the possible causes of a decrease in learning achievement is the lack of parental support for children's learning achievement. The aim of the study was to determine the effect of parental support and giving rewards on the learning achievement of fourth grade students at SD Muhammadiyah 3 Bungkal. This research is a quantitative research using ex post facto and survey methods. The subjects used were 20 grade IV students at SD Muhammadiyah 3 Bungkal. To collect data researchers used interview data collection techniques, observation, documentation, and questionnaires with data analysis techniques including tests of normality, homogeneity, linearity, and hypotheses. The results of this study showed that the Tcount (X1) was 2.283 and (X2) 3.689 higher than Ttable 2.110. Meanwhile, the Fcount value is 9.666 > Ftable 3.59. Then the decision set in this study is that H¬0 is rejected and Ha is accepted and the R Square value is 53.2%. So that it can be interpreted that there is a positive influence between the variables of parental support, reward giving, and learning achievement that is equal to 53.2%.